Bladder Pain Syndome/Interstitial Cystitis due to Pudendal Nerve Compression: Described in 1915—A Reminder for Treating Pelvic Pain a Century Later - Gohritz, Andreas; Dellon, Arnold Lee (Journal of Brachial Plexus and Peripheral Nerve Injury, 2020)
Background Interstitial cystitis (IC) or bladder pain syndrome (BPS) is highly painful and disabling and probably the most misdiagnosed urologic condition. Its classic symptoms of perineal pain, urinary urgency, and frequency despite sterile urine cultures were already described more than a century ago in a report on soldiers during World War (WW) I due to chronic pudendal nerve compression.Objectives This article translates a report from 1915 on pudendal neuropathy and discusses its author Georg Zülzer (1870–1949).Methods An English translation of the German original is provided with the biography and work of Zülzer, his clinical observations are discussed regarding modern diagnosis and therapy of pudendal nerve compression.Results In his article entitled “Irritation of the Pudendal Nerve (Neuralgia). A Frequent Clinical Picture during War Feigning Bladder Catarrh,” Zülzer describes his observation of soldiers during WW I, presenting with a triad of perineal pain, urinary urgency, and frequency despite sterile urine cultures excluding urinary infections. He also documented a characteristic skin hypersensibility of the perineum in a rhomboid shape which corresponds to the innervation area of the pudendal nerve with its two branches deriving from the “pudendal plexus.” He regards this symptomology as rare during peace, but as disease of trench warfare which can be easily diagnosed regarding clear urine and a painful skin island overlying the area of the pudendal nerve as tested by simple needle examination. Zülzer, born in Germany, was forced to emigrate to the United States in 1934, was also an important pioneer of diabetes research using pancreas extracts from dogs as early as 1907.Conclusion In this historical description, dating from about a century ago, Georg Zülzer probably gave the first exact clinical description of symptoms due to pudendal nerve compression. Pudendal nerve compression should always be taken into account when examining and treating patients with symptoms of IC/BPS.
Keywords: bladder pain syndrome; interstitial cystitis; pudendal nerve; compression; Georg Zülzer